Step-by-step explanation:
Ermm you're gonna have to write the entire question here for assistance
Answer:
-3x+3
Step-by-step explanation:
ion like workin it out but dere you go
The formula that explain the arithmetic sequence is ![a_{n}=\frac{3}{7}n-\frac{9}{7}](https://tex.z-dn.net/?f=a_%7Bn%7D%3D%5Cfrac%7B3%7D%7B7%7Dn-%5Cfrac%7B9%7D%7B7%7D)
Step-by-step explanation:
The formula of the nth term in an arithmetic sequence is
, where
- a is the first term
- d is the common difference between the consecutive terms
∵
,
, 0 ,
are some terms of an arithmetic sequence
∵ The difference between two consecutive terms =
- ![\frac{-6}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-6%7D%7B7%7D)
∴ The difference between two consecutive terms =
+
= ![\frac{3}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B7%7D)
∴ The common difference = ![\frac{3}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B7%7D)
∴ d = ![\frac{3}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B7%7D)
∵ The first term is ![\frac{-6}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-6%7D%7B7%7D)
∴ a = ![\frac{-6}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-6%7D%7B7%7D)
- Substitute a and d in the formula above
∴ ![a_{n}=\frac{-6}{7}+(n-1)\frac{3}{7}](https://tex.z-dn.net/?f=a_%7Bn%7D%3D%5Cfrac%7B-6%7D%7B7%7D%2B%28n-1%29%5Cfrac%7B3%7D%7B7%7D)
- Simplify the right hand side
∴ ![a_{n}=\frac{-6}{7}+\frac{3}{7}n-\frac{3}{7}](https://tex.z-dn.net/?f=a_%7Bn%7D%3D%5Cfrac%7B-6%7D%7B7%7D%2B%5Cfrac%7B3%7D%7B7%7Dn-%5Cfrac%7B3%7D%7B7%7D)
- Add like terms
∴ ![a_{n}=\frac{3}{7}n-\frac{9}{7}](https://tex.z-dn.net/?f=a_%7Bn%7D%3D%5Cfrac%7B3%7D%7B7%7Dn-%5Cfrac%7B9%7D%7B7%7D)
The formula that explain the arithmetic sequence is ![a_{n}=\frac{3}{7}n-\frac{9}{7}](https://tex.z-dn.net/?f=a_%7Bn%7D%3D%5Cfrac%7B3%7D%7B7%7Dn-%5Cfrac%7B9%7D%7B7%7D)
Learn more:
You can learn more about the sequences in brainly.com/question/7221312
#LearnwithBrainly